Allocating deceased donors using local vs. imported renal allografts: Logistics are more important than distance - Mahmoudreza Moein; Praise E. Njoku Austin; Rauf Shahbazov; Matthew Hanlon; Alex Almonte; Oleh Pankewycz; Mark R. Laftavi; Reza F. Saidi (Surgery in Practice and Science, 2023)
Background: The deceased donor kidney allocation system (KAS) aims to optimize and equalize organ access for candidates nationwide and facilitate organ matching for candidates who are harder to match due to biological reasons. In March 2021, UNOS implanted a new allocation of KT based on distance from the donor hospitals. A distance within 250 nautical miles will receive additional proximity points to access KT. Material and Method: This retrospective single-center study assessed the Cold ischemic time (CIT) and Delayed graft function (DGF) in allograft kidneys from January 2014 to December 2020. We studied 221 import KT, compared the outcomes to locally procured KT (n = 160), and finally compared the patients and graft survival rates in 1-year and 5-years. Results: Donor and recipient demographics were similar in both groups. Induction and maintenance immunosuppression was similar in both groups. CIT was significantly higher in the imported group (27.6 vs. 15.9 h, p< 0.0001). However, distance did not impact CIT significantly (R2= 0.07) in the imported KTs. Distance also did not impact the rate of DGF in both groups (imported 21% vs. 22%, p = 0.74). Patient and graft survivals were similar in the imported vs. local group. Conclusions: We conclude that distance alone does not correlate with CIT and DGF and it is not a great single predictable factor for the outcomes. There are many logistical factors and OPO factors that have a significant impact on CIT and DGF occurrence, which should be considered, and the new UNOS allocation changes can help in terms of equal distribution of available allografts.